Denmark : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that economic growth in Denmark slowed significantly during 2001 as domestic demand weakened and exports were hit by the global economic slowdown. Unemployment remained low and wage growth was somewhat faster than in euro area partner countries. However, price inflation was subdued. Monetary conditions were eased during 2001 as Danish interest rates generally followed those of the European Central Bank downward. The 2002 budget implies a broadly neutral fiscal stance with the surplus projected to remain within the medium-term target of 1.5-2.5 percent of GDP.